The complete chloroplast genome sequences of potato wild relative species, Solanum commersonii. Issue 1 (1st January 2016) - Cho, Kwang-Soo; Hong, Su-Young; Cho, Ji-Hong; Im, Ju-Seong; Kim, Kyunghee; Oh Lee, Hyun; Jin, Yong-Ik; Mekapogu, Manjulatha; Jang, Dong-Chil
Abstract: Solanum commersonii Dunal is a well-known wild potato belonging to Solanaceae family and commonly used as materials for somatic hybridization due to various biotic and abiotic stress resistances. The complete chloroplast genome of S. commersonii was constituted by de novo assembly using a small amount of whole genome sequencing data. The chloroplast genome of S. commersonii was 155 525 bp in length, consisted of 86 013 bp of large single copy, 18 366 bp of small single copy region and 25 573 bp of a pair of inverted repeats. A total of 113 genes were annotated including 79 protein-coding genes, 30 tRNA genes and four rRNA genes. Maximum likelihood phylogenetic analysis with 14 Solanaceae species revealed that S. commersonii is much closely related to Solanum tuberosum and S. bulbocastanum.